(3GdeONd Edi cJGH LGdjfhS aj GdCOhjI GdeaQOIs
(3ChdgG (B:s
(3GdebGdI GdChdi bGd (B: (3Ef ef GdfGS ef RYe Cf bhI GdCOhjI EfeG JYQa ef Gddhf , hde jUObhG , hPdc Cage fSHhG Gddhf GdCHjV Edi GdHQhOI , hGddhf GdCMeQ Edi GdMQGQI s
(3BNQgG (B:s
(3JeJ GdebGdI GdYGTQI ef YTQI ebGdGJ dLGdjfhS HMSH GdehGVY GdCdeI hJe GdcJGH HYhf Gddg hefg hUdi Gddg Ydi eMeO hBdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3hgh KdGK ebGdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH dGKGfi (B- (3U (B228 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs